THE USE OF CONTEXT CLUES STRATEGY FOR IMPROVING STUDENTS’ READING COMPREHENSION - Sepang, Julio (Faculty of Language and Arts (Fakultas Bahasa dan Seni) Universitas Negeri Manado, 2024)
Most students in Indonesia found difficulties while reading English Language text. They were still lacks reading comprehension skills because of two things: English was not their first language and the cultural differences that made them hard to understand certain vocabulary in the English text. Quantitative Research were used in this study. Bryman (2016) explained that Quantitative research relies on the collection analysis of the data which was based on a method of logical method and it focuses on theory testing. Students of English Education Department in Universitas Negeri Manado was the subject of this research. 28 students participated in this study. The result of SPSS ver. 20 were used to determine the result of the research. The mean score of the pre-test was 64.18 while the post-test after using the Context Clues treatment is 73.43, the sig. value of this study was 0.000 < 0.05 which means the hypothesis of Context clues strategy is accepted. This study showed why using Context Clues strategy really positively influenced students' reading comprehension skills.